Adaptability analysis of Leucaena collinsii in the microbasin Tula, Mexico - Buendía-Espinoza, Julio Cesar; Díaz-Aguilar, Irma; Cahuich-Damián, Jesús Eduardo; Morales-García, Arturo; Martínez-Hernández, Pedro Arturo; Zamora-Elizalde, Mayra Clementina (Revista Mexicana de Ciencias Agrícolas, 2020)
In recent decades, the deterioration of natural resources in Mexico has increased due to changes in land use and increasing urbanization in areas of high ecological vulnerability and low levels of productivity. The Tula micro-basin, Mexico is located in a semi-dry climate zone where soil degradation and population increase are having a strong impact on soil conservation. The objective of this study was to determine the areas suitable for the optimal development of the Leucaena collinsii Britton & Rose species in the Tula microbasin, through the maximum entropy ecological niche model, MaxEnt, for soil rehabilitation purposes. For the modeling, 19 environmental variables and 8 presence records were used, obtained from the GBIF and MEXU databases. The modeling results indicated that the variables with the greatest contribution were temperature and evapotranspiration, and that the model has a good predictive capacity (p-value= 0.013), according to the significance test with a level α= 0.05, based on the Jackniffie technique. In the model, the potential distribution of the species was low, with just 8% of the surface of the micro-basin, but a high survival (100%) was recorded, in the experimental validation. It was concluded that there are few adaptability zones for the species, in the Tula microbasin; however, its high survival in the experimental plot, determined that its introduction is an option for soil rehabilitation.
Keywords: ecological niche modeling; potential distribution; rehabilitation; soil degradation